Implementation of Goesmart Social Networking Site as a Learning Media In Ict Subjects For Students Class VII - Lantang, Fazmi Al Astari; Ramly, Rizal Arizaldy; P, Suhenrik (Department of Educational Technology, Postgraduate Program, State University of Makassar, 2025)
The development of the digital era has led to a paradigm shift in education, transitioning from traditional methods to more modern approaches. This shift directly impacts the quality of education in Indonesia, aiming to produce superior human resources with strong character and clear future vision. This study aims to examine the effectiveness of using Nearpod as a learning medium in the Information and Communication Technology (ICT) subject at SMPN 26 Makassar. A quantitative approach with a One Group Pretest-Posttest design was used, involving 30 students who were tested before and after the intervention using Nearpod. The results showed a significant improvement in student learning outcomes, with the pretest average score being 67.9 and the posttest average score being 86. The t-test revealed a t-value of 6.411, which was higher than the critical t-value of 1.699, indicating the rejection of the null hypothesis and acceptance of the alternative hypothesis. This finding demonstrates that the use of Nearpod effectively improves student learning outcomes in the ICT subject. This research contributes to the development of more engaging, interactive, and digitally-based learning strategies, aligning with the needs of today's digital generation